2012
DOI: 10.5539/ijc.v4n3p42
|View full text |Cite
|
Sign up to set email alerts
|

Efficient DNA Cleavage Induced by RhIII(TMPyP)5+ in the Presence of Ascorbic Acid

Abstract: The ability of Rh(III) tetrakis-N-methylpyridyl porphyrin, Rh III (TMPyP) 5+ , to interact with and cleave DNA was, investigated by UV-visible, luminescence, circular dichroism (CD), electron spin resonance (ESR) and gel electrophoresis methods in the presence or absence of ascorbic acid. UV-absorption data showed that Rh III (TMPyP) 5+ is capable of interacting with DNA, as indicated by the appearance of a red shift and hypochromicity of the Soret band. The CD data revealed that Rh III (TMPyP) 5+ was capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…26 As such, several approaches have been explored to enhance its therapeutic outcome in PDT, including PS formulations containing combinations of TMPyP and other hydrophilic PSs, 151,159 conjugations of TMPyP with graphene oxide, 158,163 Au, [164][165] Ag, [166][167] iron oxide NPs, [168][169] nanoencapsulation 170 and metalation with biologically active metals. 156,[171][172][173][174] TMPyP has a net charge of four units which imparts to its necessary hydrophilicity for photobiological applications. However, numerous publications have suggested that PSs bear a combination of high cationic charges and that added lipophilicity usually translates to better therapeutic efficacy.…”
Section: Cationic Porphyrin Pssmentioning
confidence: 99%
“…26 As such, several approaches have been explored to enhance its therapeutic outcome in PDT, including PS formulations containing combinations of TMPyP and other hydrophilic PSs, 151,159 conjugations of TMPyP with graphene oxide, 158,163 Au, [164][165] Ag, [166][167] iron oxide NPs, [168][169] nanoencapsulation 170 and metalation with biologically active metals. 156,[171][172][173][174] TMPyP has a net charge of four units which imparts to its necessary hydrophilicity for photobiological applications. However, numerous publications have suggested that PSs bear a combination of high cationic charges and that added lipophilicity usually translates to better therapeutic efficacy.…”
Section: Cationic Porphyrin Pssmentioning
confidence: 99%